2016
DOI: 10.21276/ap.2016.5.2.4
|View full text |Cite
|
Sign up to set email alerts
|

An open label, randomized, multicenter, comparative, three arm Phase II clinical study to evaluate the safety and efficacy of mixture of five species of Ocimum in subjects with acute common cold

Abstract: Ba sil and its variou s species are known to ha ve an effect on common cold and possess immunomodulatory properties. This paper describes a clinical trial of a herbal formulation, Panchtulasi drops in acute common cold; the formulation consists of essential oils of five species of ocimum, namely; Ocimum sanctum Linn., Ocimum basilicum Linn., Ocimum gratissimum Linn., Ocimum citriodorum Linn. and Ocimum canum Linn.This was an open label, three arm Phase II study to determine the safety and effica cy of Panchatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
2
0
0
Order By: Relevance
“…The analysis of WURSS‐24 revealed that the separate score of domains 3 and 4 of this questionnaire (score for cold specific functional impairment and change in global cold severity, respectively) and the total score significantly decreased in patients who consumed nanocurcumin supplements. Previous studies have revealed the potential efficacy of herbal extracts rich in polyphenols such as a combination of ginger and goldenrod extracts and various species of basil in alleviating symptoms of similar diseases like common cold measured by WURSS, which is in line with our results (Guay, Champagne, Guibord, & Gruenwald, 2012; Shelke et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The analysis of WURSS‐24 revealed that the separate score of domains 3 and 4 of this questionnaire (score for cold specific functional impairment and change in global cold severity, respectively) and the total score significantly decreased in patients who consumed nanocurcumin supplements. Previous studies have revealed the potential efficacy of herbal extracts rich in polyphenols such as a combination of ginger and goldenrod extracts and various species of basil in alleviating symptoms of similar diseases like common cold measured by WURSS, which is in line with our results (Guay, Champagne, Guibord, & Gruenwald, 2012; Shelke et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…of domains 3 and 4 of this questionnaire (score for cold specific functional impairment and change in global cold severity, respectively) and the total score significantly decreased in patients who consumed nanocurcumin supplements. Previous studies have revealed the potential efficacy of herbal extracts rich in polyphenols such as a combination of ginger and goldenrod extracts and various species of basil in alleviating symptoms of similar diseases like common cold measured by WURSS, which is in line with our results(Guay, Champagne, Guibord, & Gruenwald, 2012;Shelke et al, 2016).The radiological findings of our study did not show any significant differences in the score of pulmonary involvement by SARS-CoV-2 between the nanocurcumin and placebo groups. CT findings obtained from COVID-19 patients have shown that at the early stages of the disease (0-4 days), mainly the lower zones of the lungs are involved with ground-glass opacity and its subtypes.…”
supporting
confidence: 93%